Implementation of Android-Based Learning Media in ICT Subject for Grade VII at SMP Negeri 11 OKU - Sutiono, Edi; Joko Kuswanto; Devana, Trisilia (TIERS Information Technology Journal, 2024)
The learning process in schools is often less interesting because the methods used tend to be conventional and less relevant to the learning style of the current digital generation. Therefore, innovative learning media that can support the learning process is needed, one of which is android-based. This research aims to develop android-based learning multimedia in grade VII ICT subjects at SMP Negeri 11 OKU. The research method used is development research with the ADDIE model approach. Based on the several stages of testing carried out, data was obtained of 100% for its appearance or function and data on student responses were obtained of 83.4% with very good criteria. Based on the results of the study, it can be concluded that multimedia learning is feasible and can be used as an alternative media during the learning process. The existence of android-based learning multimedia can motivate students to learn and enable students to learn independently according to their abilities anywhere and anytime.